THE RELATIONSHIP OF THE STUDENTS’ PERCEPTION ON THE CAMPUS LEARNING ENVIRONMENT AND THEIR GPA IN SCHOOL OF MEDICINE OF MULAWARMAN UNIVERSITY - Achmad Ferdinan Amrullah; Sulistiawati Sulistiawati; Cicih Bhakti Purnamasari (Universitas Muhammadiyah Kalimantan Timur, 2020)
The success of the student learning process is characterized by academic achievement. One of the factors that can affect academic achievement is the learning environment. This study aims to determine the relationship of the students’ perception on the campus learning environment and their GPA in school of medicine of Mulawarman University. This research is an observational analytic study with cross sectional method. The research respondents were students of the Medicine Study Program of the School of Medicine in Mulawarman University by using total sample technique. The method of data analysis used descriptive data analysis and the analytic data analysis used chi square test. There were 316 respondents who met the inclusion and exclusion criteria, male respondents were 91 people (28.8%) and female respondents were 225 people (71.2%). As many as 268 students (84.8%) had more positive than negative perception on the campus learning environment, while as many as 232 students (73.4%) got good category for the grade point. The results of the study obtained p=0.000. In conclusion, there is a relationship between student perceptions of the learning environment on campus with an grade point.